Landslides Causes and Treatment in the Darjeeling Hills - A Case Study - Rai, M. S. (Indian Forester, 2006)
The Darjeeling Hills are subjected to landslides of minor or major intensities almost annually during the rainy season, the apparent cause being continuous rainfall of heavy intensities because most of the landslides in the past having occurred after continuous and heavy rainfall, the other causes of the landslides are young geological formation, shallow soil devoid of soil cover and at times tectonic movement. Some of the landslides may heal up in course of time but some pose problems to the local habitation and communication system year after year. One such problematic area at Mongwa in Darjeeling district was taken up for treatment. Giving due consideration to local factors and land treatment by way of construction of palisades and then planting fodder and tree species including bamboo in pits with enriched soil, the exposed area could be covered with crown canopy in one season itself thereby stabilizing the area. The local people were taken into confidence and their participation in closing the area against grazing was ensured by promising them fodder and bamboo which were planted in the area.